2023
DOI: 10.1186/s12886-023-02942-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biometric indicators of anterior segment parameters after ICL implantation by swept-source optical coherence tomography

Abstract: Background To evaluate anterior segment structural alterations after implantable collamer lens (ICL) implantation in myopic patients using swept-source quantitative optical coherence tomography (SS-OCT). Methods This prospective study included 47 eyes in 24 patients with preoperative spherical equivalent ≥ -3.00 D. Patients underwent ICL implantation at Department of Ophthalmology, Peking University Third Hospital, from May 2021 to December 2022. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This was the first study to compare ACA500 and AOD500 after phakic IOL implantation, which has been exclusively addressed in existing literature on glaucoma. [ 23 , 31 ] In our study, we observed a significant decrease in the ACA and AOD parameters at 12 months after surgery compared to before the operation. There were no significant differences in the ACA and AOD values observed between ICL and IPCL implantation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This was the first study to compare ACA500 and AOD500 after phakic IOL implantation, which has been exclusively addressed in existing literature on glaucoma. [ 23 , 31 ] In our study, we observed a significant decrease in the ACA and AOD parameters at 12 months after surgery compared to before the operation. There were no significant differences in the ACA and AOD values observed between ICL and IPCL implantation.…”
Section: Discussionsupporting
confidence: 56%
“…[ 23 , 30 ] The AOD500 is the distance from the posterior cornea surface and the anterior iris surface, which is measured on a line perpendicular to the trabecular meshwork 500 μm from the scleral spur. [ 23 , 30 , 31 ] The measures of ACA500 and AOD500 are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Where device availability permits, intraoperative use of OCT assisted ICL implantation helps to achieve the ideal vault ( 34 ). After ICL implantation, regular observation of vault changes using slit-lamp microscopy and AS-OCT can help prevent early elevated IOP and glaucoma, thus avoiding late-stage vision impairment ( 35 ). Figure 3 shows observation of lens vault using slit lamp after ICL implantation.…”
Section: Excessive Icl Vaultmentioning
confidence: 99%
“…Lin et al noted decreased central anterior chamber depth (CACD) and anterior chamber volume (ACV) postoperatively, with stabilization observed over time, while Tang et al found reductions in anterior chamber angle parameters one month post-ICL implantation. These ndings show the need for long-term monitoring of anterior chamber parameters after ICL implantation to ensure patients have long-term ocular health [12,13].…”
mentioning
confidence: 99%